Windpipe Controls Drosophila Intestinal Homeostasis by Regulating JAK/STAT Pathway via Promoting Receptor Endocytosis and Lysosomal Degradation - Ren W. (Public Library of Science (PloS), 2018)
10.1371/journal.pgen.1005180